Ireland - O'Connor, Emmet (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2002)
Abstract Modern Irish labour history dates from the mid 1970s, years that saw the foundation of the Irish Labour History Society in 1973 and the launch of its annual journal, Saothar in 1975. While steady progress has since been made, the subject suffers from a popular perception of labour as marginal, a reluctance within the trade union movement to recover its often fractious past, and academic neglect. Ireland was not deeply affected by the “crisis” in labour history in the 1990s. It is likely that the flow of publications will continue. But without full-time practitioners, progress in method and theory will be patchy.